2019
DOI: 10.4103/jfmpc.jfmpc_95_19
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis knowledge and beliefs among postmenopausal women: A cross-sectional study from a teaching hospital in southern India

Abstract: Objectives: Osteoporosis continues to be underrecognized in many parts of India. This study was undertaken to assess the level of knowledge of osteoporosis among postmenopausal women referred for a dual-energy X-ray absorptiometry (DXA) scan in a teaching hospital in southern India. Methodology: This cross-sectional study assessed the state of awareness in consecutive postmenopausal women referred for a DXA scan using a validated questionnaire – Osteoporosis Knowledge A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…The participants of our study had poor knowledge about the risk factors and the consequences of osteoporosis and the findings show that 50% of the participants had attained adequate knowledge with a median score of 12 and the remaining half of the participants attained less than 12, and they are with inadequate knowledge. A similar deficit in knowledge was observed in a study conducted by Senthilraja et al, 11 where 60% of participants had very poor knowledge.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The participants of our study had poor knowledge about the risk factors and the consequences of osteoporosis and the findings show that 50% of the participants had attained adequate knowledge with a median score of 12 and the remaining half of the participants attained less than 12, and they are with inadequate knowledge. A similar deficit in knowledge was observed in a study conducted by Senthilraja et al, 11 where 60% of participants had very poor knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…Study conducted by Senthilraja et al 11 demonstrates that the mean age of attainment of menopause was 46 years. This is consistent with another study conducted by Ahuja 12 in which the average age of menopause of an Indian woman was 46.2 years.…”
Section: Discussionmentioning
confidence: 96%
“…[ 21 ] Few authors from India reported poor awareness of osteoporosis in postmenopausal women are noted. [ 18 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of awareness, these individuals are likely to remain unaware of their susceptibility to developing osteoporosis. They might not consider requesting diagnostic examinations, adopting preventive measures against the onset of the disease, or recognizing that osteoporosis can commence well before the onset of menopause [12]. Consequently, they could mistakenly believe that preventive actions only become relevant after menopause.…”
Section: Introductionmentioning
confidence: 99%